Design of automatic truck axle counter using deep learning on NVIDIA Jetson Nano / Rakhmad Gusta Putra... [et.al.] - Putra, Rakhmad Gusta P; Pribadi, Wahyu; Juliando Sudirman, Dirvi Eko; Subkhan, Muhamad Fajar (2023)
To improve the quality of transportation, it is necessary to make right decisions based on accurate data. The flow of vehicles is important in the planning and operation of new roads and the modification of existing roads is needed to meet changes in traffic conditions. To get information about traffic characteristics, various information about traffic infrastructure and driver behavior is needed. The information obtained is analyzed to obtain traffic workload results. If the workload results are below the minimum service standard, a geometric change or arrangement of road space usage is required. The calculation of the number and classification of vehicles has been done manually at certain times.